2007
DOI: 10.1108/14720700710820588
|View full text |Cite
|
Sign up to set email alerts
|

SME social performance: a four‐cell typology of key drivers and barriers on social issues and their implications for stakeholder theory

Abstract: PurposeSmall and medium enterprises (SMEs) are often neglected in the context of business and society theory building. The purpose of this article is to build a model of why SMEs address social issues by integrating internal and external drivers and barriers to social performance (SP).Design/methodology/approachUsing thematic analysis, barriers and drivers to SME social performance are clustered along key stakeholders and presented in a theoretical model. The analysis dates from 1973 until 2006 and is grounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 25 publications
1
71
0
4
Order By: Relevance
“…Numerous studies have shown a similar distinct pattern among SMEs involved in business SR. SME managers are highly committed at a personal level to principles of public responsibility, concern for social issues, and a sense of reciprocity or 'giving back' to society (Jamali et al 2008, Fuller and Tian 2006, Jenkins 2006, Kusyk and Lozano 2007. Perceived benefits among SME owners and managers are far more aligned with altruistic dimensions such as participation, a sense of pride and integrity (Jenkins 2006) than with economic benefits.…”
Section: Challenges In Business Sr Practicementioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have shown a similar distinct pattern among SMEs involved in business SR. SME managers are highly committed at a personal level to principles of public responsibility, concern for social issues, and a sense of reciprocity or 'giving back' to society (Jamali et al 2008, Fuller and Tian 2006, Jenkins 2006, Kusyk and Lozano 2007. Perceived benefits among SME owners and managers are far more aligned with altruistic dimensions such as participation, a sense of pride and integrity (Jenkins 2006) than with economic benefits.…”
Section: Challenges In Business Sr Practicementioning
confidence: 99%
“…Indeed small business owners have distanced themselves perhaps understandably from association with the 'corporate' in CSR 1 , suggesting that current language and debates for business SR as well as its understandings and prescription may require reconceptualization for small business (Lange and Fenwick 2007;Jamali et al 2008, Jenkins 2004. Finally, analysts of CSR in SMEs agree that, particularly given the importance of SMEs to most national economies, the area requires further empirical research on several dimensions (Jenkins 2006, Lepoutre and Heene 2006, Kusyk and Lozano 2007, Murillo and Lozano 2006, Spence 2007). …”
Section: Learning To Practice Social Responsibility In Small Businessmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the current SME literature itself the groupings identified are recognised but as separate areas. For instance, concerning governance and SMEs, see Abor & Biekpe (2007) and Gray (2006); for employees, see Devins et al (2004) and Bacon & Hoque (2005); for stakeholder relationships, see Kusyk & Lozano (2007); and for reporting, see Fassin (2008). Drawing these previously discrete groupings together provides a suggested framework with a holistic view of RBP in SMEs.…”
Section: Criteria For Rbp In Smesmentioning
confidence: 99%